The prevalence, correlates, and clinical implications of hoarding behaviors in high-functioning autism - Mohamed Abouzed; Amjad Gabr; Khaled A. Elag; Mahmoud Soliman; Nisrin Elsaadouni; Nasr Abou Elzahab; Mostafa Barakat; Ashraf Elsherbiny (Scientific Reports)
Abstract This study aimed to investigate the relationships between hoarding behaviors, autism characteristics, and demographic factors in adults diagnosed with high-functioning ASD (Autism Spectrum Disorder). A total of 112 adults, aged 18–35, with high-functioning ASD completed self-reported assessments on hoarding (Savings Inventory-Revised; SI-R) and autism traits (Autism-Spectrum Quotient; AQ). Additionally, demographic data was gathered. Correlation and regression analyses were performed. The findings revealed positive correlations between hoarding and overall autism traits. Autism quotient scores accounted for 24% of the variance in hoarding inventory scores. Higher AQ scores were associated with increased SI-R scores. Specific AQ subscales were linked to particular SI-R subscales. Gender, age, education level, and employment status were connected to assessment scores. A multiple regression analysis revealed that demographic variables accounted for 19% of the variance in hoarding severity. Gender was found to moderate the impact of age on hoarding behaviors. Significant associations were identified between hoarding tendencies and autism traits in adults with ASD. Demographic variables also played a role in symptom presentation. These findings shed light on the relationship between autism characteristics and hoarding behaviors, as well as how external factors influence them. Further research is necessary to enhance understanding and guide interventions for hoarding in ASD populations.